CT perfusion imaging in aneurysmal subarachnoid hemorrhage. State of the art - Lolli, Valentina Elisabetta; Guenego, Adrien; Sadeghi, Niloufar; Jodaitis, Lise; Lubicz, Boris; Taccone, Fabio Silvio; Gouvea Bogossian, Elisa (Frontiers in Radiology, 2024)
CT perfusion (CTP) images can be easily and rapidly obtained on all modern CT scanners and have become part of the routine imaging protocol of patients with aneurysmal subarachnoid haemorrhage (aSAH). There is a growing body of evidence supporting the use of CTP imaging in these patients, however, there are significant differences in the software packages and methods of analysing CTP. In. addition, no quantitative threshold values for tissue at risk (TAR) have been validated in this patients' population. Here we discuss the contribution of the technique in the identification of patients at risk of aSAH-related delayed cerebral ischemia (DCI) and in the assessment of the response to endovascular rescue therapy (ERT). We also address the limitations and pitfalls of automated CTP postprocessing that are specific to aSAH patients as compared to acute ischemic stroke (AIS).